DIFFERENCES OF QIRĀ'ĀT IN TAṢRĪF AL-AF'ĀL AND ITS IMPLICATIONS FOR THE INTERPRETATION OF THE QUR'AN: THEOLOGICAL AND JURIDICAL ANALYSIS - Siti Yuliati; Nanda Sagita; Abdur Rokhim Hasan (Fakultas Ushuluddin dan Pemikiran Islam, Universitas PTIQ Jakarta, 2026)
This article examines the differences in qirā’āt within taṣrīf al-af‘āl (verbal morphology) and their implications for the construction of Qur’anic interpretation in both theological and juridical domains. This study is motivated by the academic problem that qirā’āt studies have often been reduced to a merely phonetic discipline, with limited exploration of their exegetical implications. This research employs a qualitative approach using library research methods and descriptive-comparative analysis of Qur’anic verses that exhibit variations in verbal forms. The findings reveal that differences in taṣrīf al-af‘āl—including variations in ṣīghah (verbal forms), wazan (patterns), bina’ (voice), and pronouns—extend beyond linguistic aspects and significantly influence the construction of theological meanings and the formulation of Islamic legal rulings. This article argues that qirā’āt function as an internal hermeneutical mechanism of the Qur’an, enriching and expanding meaning without generating contradiction